Smuggling Of Illegal Indonesian Workers In Malaysia - Hilda Savitri (PT Syamilah Literasi Islami, 2024)
Indonesia is a country close to Malaysia, making it easier for illegal migrant workers to enter Malaysia to work illegally. One of the factors for the occurrence of this illegal migrant worker case is the lack of education so that the surrounding community lacks jobs in Indonesia which makes them go to Malaysia to get a job even though the job is illegal. Then the next factor is the difference in higher salaries in Malaysia compared to Indonesia. The Indonesian government's efforts are to provide various ways to overcome it such as legal protection from the Indonesian Embassy which has direct responsibility for the problem of illegal migrant workers. This research discusses the smuggling of illegal Indonesian workers in Malaysia which will discuss the factors that influence the emergence of illegal workers, the impact caused by illegal workers, as well as the laws given to these illegal workers, and the government's response from both countries regarding this case. by using qualitative methods based on literature studies and online searches to obtain information.